2020
DOI: 10.1021/acsami.0c07931
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of the LiNi0.8Co0.1Mn0.1O2 Cathode Material by Coating with FePO4 with a Yolk–Shell Structure for Improved Electrochemical Performance

Abstract: Coating with FePO 4 with the size of 20−30 nm on the surface of a LiNi 0.8 Co 0.10 Mn 0.1 O 2 (NCM811) cathode produces an LFP3@NCM811 cathode via a sol−gel method, which markedly reduces secondary crystal cracking. A stable particle structure greatly improves the cycling stability of the LFP3@ NCM811cathode, which retains 97% of its initial discharge capacity compared to NCM811 (78%) after 100 cycles at 2.7−4.5 V. Furthermore, it retains 86 and 63% of its initial discharge capacity after 400 cycles for LFP3@N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Owing to the improved charge transfer at the cathode-electrolyte interface, NCM-2 exhibits the highest capacities at all current densities, that is, 211.4, 204.4, 190.0, 178.2, 160.0, 141.0, and 112.6 mA h g -1 from 0.25, 0.5, 1.25, 2.5, 6.25, 12.5 to 25.0 C, respectively, which are higher than those for NCM-0 (i.e., 201.8, 191.3, 175.2, 161.1, 141.0, 120.9, and 93.1 mA h g -1 ). Further, compared with the previously reported NCM charged to 4.5 V at the room temperature, [26,[34][35][36][37][38][39][40][41][42] the electrochemical performance of the pristine NCM in this work is normal in the initial discharge capacity (Table S2, Supporting Information) and the optimized sample exhibits the outstanding rate capability (Table S3 and Figure S6, Supporting Information). These indicate that our modification strategy for NCM has an excellent effect on improving the performance of NCM.…”
Section: Improved Electrochemical Performancementioning
confidence: 61%
“…Owing to the improved charge transfer at the cathode-electrolyte interface, NCM-2 exhibits the highest capacities at all current densities, that is, 211.4, 204.4, 190.0, 178.2, 160.0, 141.0, and 112.6 mA h g -1 from 0.25, 0.5, 1.25, 2.5, 6.25, 12.5 to 25.0 C, respectively, which are higher than those for NCM-0 (i.e., 201.8, 191.3, 175.2, 161.1, 141.0, 120.9, and 93.1 mA h g -1 ). Further, compared with the previously reported NCM charged to 4.5 V at the room temperature, [26,[34][35][36][37][38][39][40][41][42] the electrochemical performance of the pristine NCM in this work is normal in the initial discharge capacity (Table S2, Supporting Information) and the optimized sample exhibits the outstanding rate capability (Table S3 and Figure S6, Supporting Information). These indicate that our modification strategy for NCM has an excellent effect on improving the performance of NCM.…”
Section: Improved Electrochemical Performancementioning
confidence: 61%
“…Coating with another phosphate, FePO 4 , which was shown to improve the electrochemical properties of NCA [108] was also probed with NCM811. The FePO 4 -coated NCM811 powders prepared via a sol-gel method demonstrated a capacity retention of 97% after 100 cycles and 86% after 400 cycles at 0.2 C [188]. Since FePO 4 is a good conductor, the rate capability was also increased, with a capacity maintained at 151.4 mAh g −1 at 5 C. LaPO 4 -coated NCM811 demonstrated 91.2% after 100 cycles at 1 C [189], but has not been tested at 5 C. However, since LaPO 4 is an insulator, the rate capability is expected to be reduced, with respect to that of FePO 4 -coated NCM811.…”
Section: Coating Ncmmentioning
confidence: 99%
“…Compared with the measures to solve the problem from the material aspects, such as doping, [16–19] coating [20–23] and compounding, [24,25] adding functional additives [14,26] into the electrolyte is more efficient and economic [27,28] . It is shown that during the initial cycle of the LIBs, an interface layer rich with organic/inorganic salts will be formed at the interfaces between the electrodes and the electrolyte [29] .…”
Section: Introductionmentioning
confidence: 99%